ACEHNESE WOMEN (A history of Acehnese Women leaders) - Sari, Rosnida (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2016)
In Acehnese history, many women held significant positions. However, the history of female Acehnese rulers is hardly written in Acehnese history, even though they give many contributions to develop Aceh as we seen now. Safiatuddin is one of very famous female ruler in Aceh and she also creates a policy that still use until now. She also was invited to other countries in Southeast Asia to give lectures and she was a queen who believe in democracy and science by not arrested the ulama who want to make coup d‟ etat. She even not put them in jail but only exiled because those ulama do not sabotage, subversive, burning, killing and other criminal things. There are others female rulers and heroines who also give their contributions in developing Aceh. However, their contributions seem forgotten in Acehnese history lesson. It becomes worst when the fatwa from Mecca saying women cannot be a leader. The New Order also contributes in making women only in domestic sphere.